Developing management skills for leadership - Parker, Chris (Prentice Hall, 2003)
This new book aims to raise the reader's awareness by identifying key personal and interpersonal management skills, and highlighting the relationships that exist between them. It also aims to increase knowledge by providing an overview and discussion of relevant management theory and research before moving to develop capability by offering a variety of practical activities